Reducing unnecessary prescriptions of antibiotics for acute cough: Adaptation of a leaflet aimed at Turkish immigrants in Germany - Fuchs Angela; Brockmann Silke; Wollny Anja; Sahlan Selime; Altiner Attila (BMC Family Practice, 2008)
Abstract Background The reduction in the number of unnecessary prescriptions of antibiotics has become one of the most important objectives for primary health care. German GPs report that they are under "pressure to prescribe" antibiotics particularly in consultations with Turkish immigrants. And so a qualitative approach was used to learn more about the socio-medical context of Turkish patients in regard to acute coughs. A German leaflet designed to improve the doctor-patient communication has been positively tested and then adapted for Turkish patients. Methods The original leaflet was first translated into Turkish. Then 57 patients belonging to 8 different GPs were interviewed about the leaflet using a semi-standardised script. The material was audio recorded, fully transcribed, and analysed by three independent researchers. As a first step a comprehensive content analysis was performed. Secondly, elements crucial to any Turkish version of the leaflet were identified. Results The interviews showed that the leaflets' messages were clearly understood by all patients irrespective of age, gender, and educational background. We identified no major problems in the perception of the translated leaflet but identified several minor points which could be improved. We found that patients were starting to reconsider their attitudes after reading the leaflet. Conclusion The leaflet successfully imparted relevant and new information to the target patients. A qualitative approach is a feasible way to prove general acceptance and provides additional information for its adaptation to medico-cultural factors.